Real convergence using TAR panel unit root tests: An application to the Southern African Development Community - Christian K. Tipoy (SPOUDAI - Journal of Economics and Business, 2019)
The African Union advocates the creation of a monetary union in stages for the entire continent starting with each of the different sub-regions. Building from that, the Southern African Development Community has, among its goals, the creation of a monetary union for its member states. However, the recent European Union crisis has sparked renewed interest in the achievement of convergence among potential member states prior to the establishment of a monetary union. We examine real convergence in per capita output of the Southern African Development Community countries using annual data from 1980 to 2017. An approach that combines threshold modelling, panel data unit root testing and critical values bootstrapping is used. The sample is divided in three sets comprising the high, middle and low-income countries. We find significant convergence among the high-income countries. However, after adding successively the middle and low-income countries to the set of highincome states, we find no evidence of convergence. These results support that the member states of this community do not conform to the optimal currency area criteria, casting doubt on the establishment of an efficient monetary union in the short run.
Keywords: C12; C33; F43; 330; Real convergence; panel data unit root test; bootstrap; threshold model; SADC